Traditional Medicinal Plants Used by the Community of Sri Wangi Village, Kapuas Hulu Regency - Fathul Yusro; Yeni Mariani (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2021)
Kapuas Hulu Regency is a Conservation District because most of its area is protected forest (National Parks and Protected Forests). The existence of people who are close to the forest makes them often interact with plants, one of which is with medicinal plants. This study aimed to analyze the types of medicinal plants used by the community of Sri Wangi Village, Boyan Tanjung District, Kapuas Hulu Regency. This study uses a survey method with data collection techniques by snowball sampling. The data collected is the types of medicinal plants used, the medicinal plants' efficacy, the parts used, processing methods, and administration methods. The results showed that the number of medicinal plants used by the community was 34 species and distributed to 19 families. The highest use is found in the leaves (30%), processed by boiling (43.59%) and used by drinking (43.59%). The data on the types of medicinal plants used by the people of Sri Wangi Village can add to the repertoire of knowledge of medicinal plants in West Kalimantan.